POLITENESS STRATEGIES OF REQUESTS USED IN MANGUPA MANDAILING WEDDING CEREMONY - Nasution, Mutia Maulidina Anzani; Lubis, Safrida (TRANSFORM: Journal of English Language Teaching and Learning, 2019)
This study aimed at analyzing the kind politeness strategy in request which represented in speech of Mangupa in Mandailing Wedding Ceremony. The descriptive qualitative method used to gain the findings of the data itself. From that findings, 18 requests from 1 speakers has been analyzed. And from those, 22 requests filtered throught transcribing the event. Of all 22 requests, it was found that there were 7 politeness strategies used, they were Mood derivable, Performatives, Hedged Performatives, Obligation Statement, Want Statement, Suggestory Formulae, Query Prepatory. Later on, the performatives was the dominant type of politeness since the Mangupa was a sacred ceremony, the using of prformatives would be found in many ways. The instrument of this study was recording the event from video recorder and transcribing them into list. And from that list, the categorization would be easy to exctract the data. Thus the writer found that positive politeness that used also similar to another local tribe wedding ceremony.